PERNIKAHAN BEDA AGAMA DALAM PERSPEKTIF HIFDZUN NASL - Salsabila, Izatul Aini; Lutfiyah, Lutfiyah (Usroh, 2024)
Interfaith marriage in Indonesia is a complex issue and often causes debate among the public. From the perspective of hifdzun nasl, which focuses on the protection and preservation of generations, interfaith marriages can be viewed from the point of view of potential conflicts in religious values that can affect the formation of children's character. This research aims to specifically analyze the principle of hifdzun nasl applied in the case of interfaith marriage and its impact on family stability and the continuation of Islamic values in offspring. This research uses a qualitative method with a normative-theological approach. The data is obtained through a literature study of the Qur'an, hadith, fiqh books, as well as the views of classical and contemporary scholars. The results show that in the perspective of hifdzun nasl, interfaith marriage has the potential to damage the continuity of aqidah and Islamic values in offspring. Thus, understanding hifdzun nasl is very important to see marriage as a bond that is not only limited to religious aspects, but also as a means to understand each other and create harmony in diversity. Therefore, people must be aware of the mafsadat of interfaith marriage in order to create a conducive environment for the sustainability of future generations.